Functional Importance of a Proteoglycan Coreceptor in Pathologic Lymphangiogenesis. Issue 2 (8th July 2016) - Johns, Scott C.; Yin, Xin; Jeltsch, Michael; Bishop, Joseph R.; Schuksz, Manuela; El Ghazal, Roland; Wilcox-Adelman, Sarah A.; Alitalo, Kari; Fuster, Mark M.
Abstract : Rationale: : Lymphatic vessel growth is mediated by major prolymphangiogenic factors, such as vascular endothelial growth factor (VEGF-C) and VEGF-D, among other endothelial effectors. Heparan sulfate is a linear polysaccharide expressed on proteoglycan core proteins on cell membranes and matrix, playing roles in angiogenesis, although little is known about any function(s) in lymphatic remodeling in vivo. Objective: : To explore the genetic basis and mechanisms, whereby heparan sulfate proteoglycans mediate pathological lymphatic remodeling. Methods and Results: : Lymphatic endothelial deficiency in the major heparan sulfate biosynthetic enzyme N -deacetylase/ N -sulfotransferase-1 (Ndst1; involved in glycan-chain sulfation) was associated with reduced lymphangiogenesis in pathological models, including spontaneous neoplasia. Mouse mutants demonstrated tumor-associated lymphatic vessels with apoptotic nuclei. Mutant lymphatic endothelia demonstrated impaired mitogen (Erk) and survival (Akt) pathway signaling and reduced VEGF-C–mediated protection from starvation-induced apoptosis. Lymphatic endothelial-specific Ndst1 deficiency (in Ndst1 f/f Prox1 +/ Cre ERT2 mice) was sufficient to inhibit VEGF-C–dependent lymphangiogenesis. Lymphatic heparan sulfate deficiency reduced phosphorylation of the major lymphatic growth receptor VEGF receptor-3 in response to multiple VEGF-C species. Syndecan-4 was the dominantly expressed heparan sulfate proteoglycan in mouse lymphatic endothelia, and pathological lymphangiogenesis was impaired in Sdc4 (−/−) mice. On the lymphatic cell surface, VEGF-C induced robust association between syndecan-4 and VEGF receptor-3, which was sensitive to glycan disruption. Moreover, VEGF receptor-3 mitogen and survival signaling was reduced in the setting of Ndst1 or Sdc4 deficiency. Conclusions: : These findings demonstrate the genetic importance of heparan sulfate and the major lymphatic proteoglycan syndecan-4 in pathological lymphatic remodeling. This may introduce novel future strategies to alter pathological lymphatic-vascular remodeling. Abstract : Supplemental Digital Content is available in the text.